KAJIAN PEMBERDAYAAN PERAN PEREMPUAN DALAM PENGELOLAAN IRIGASI DI KABUPATEN KULON PROGO - Sri Sumardiningsih (LPPM UNY, 2005)
Abstract This research aims at finding out the society’s perception on the role of P3A D1 Pengasih, on the role of women in P3A organization, and on the role of woman in P3A DI Pengasih. It also aims at finding out the improvement of women’s involvement in managing the irrigation. This research is a descriptive-explorative research. Data collection is conducted by focused group discussion (FGD), interviews, questionnaires and documentation. The result of the data analysis shows that the society in DI Pengasih has good perception on the role of P3A. There is an improvement of the women’s role in P3A. Before the effort of empowerment, the involvement of the women was only in paying the contribution fee at harvest and providing logistics when they had cooperative mass working cleaning the tertiary channel. After the implementation of the empowerment, the women play their role as members of P3A, by sharing their opinion in meetings, cleaning drains and channels, paying the contribution fee, attending the training, and using groups’ cash. There is also an improvement in human resource. Before the implementation of the empowerment, women’s access was limited to land irrigation, fertilizers, seeds, pesticides, and human power. Now, they are able to access the trainings, irrigation, fertilizers, seeds, pesticides, human power, and marketing. However, there is no improvement on the control on human resource by women. Keywords: empowerment, role, women,irrigation